(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Splenectomy has been associated with several long-term complications; pulmonary arterial hypertension has gained special attention. It seems that the absence of a spleen, rather than underlying condition for which the splenectomy was performed, is the primary cause of this condition. Objectives:Assessing the risk factors for development of pulmonary hypertension in different indications of splenectomy Method:Fifty postsplenectomy patients were included and transthoracic echocardiographic study looking for right ventricle size; ejection fraction and pulmonary artery pressure were performed for each patient in addition to complete blood count. Results:The patients’ mean age was 32.5±1.8 years. The mean duration after splenectomy was 5.2±0.34 years with a range of 1-10 years. Hemoglobinopathies in different types formed 54% (27/50) of these indications, while non hematological indications were reported in 7 cases (14%). Pulmonary arterial hypertension was reported in 22% of patients with mean pressure 30.10±1.18 mmHg. It is positively correlated with right ventricular size. The highest risk of pulmonary arterial hypertension was reported with splenectomy due to hemolytic diseases in comparison with other indication despite persistence of similar risk in non hemolytic indication but of no statistical significance. The more severe degree of anemia has negative correlation with pulmonary arterial hypertension as well as high WBC count unlike thrombocytosis. Conclusion:Whatever the underlying indications of splenectomy, the risk of pulmonary hypertension exists, which may not related only to thrombocytosis but also for anemia and leucocytosis and it needs long duration follow up to be diagnosed. Key words: Splenectomy, pulmonary hypertension.